Genetic Improvement to Obtain Specialized Haematococcus pluvialis Genotypes for the Production of Carotenoids, with Particular Reference to Astaxanthin - Rosa Paola Radice; Maria Carmela Padula; Angelica Liguori; Gabriele D’Arienzo; Giuseppe Martelli (International Journal of Plant Biology, 2023)
Nowadays, the search for natural substances with a high nutraceutical effect positively impact the world market. Among the most attractive macromolecules are antioxidants, capable of preventing the development of various pathologies. Astaxanthin (ASX) is antioxidant molecule produced by the microalga H. pluvialis as a response to different types of stress. Usually, astaxanthin production involves the first phase of accumulation of the biomass of H. pluvialis (green phase), which is then stressed to stimulate the biosynthesis and accumulation of ASX (red phase). In this study, the H. pluvialis wild-type strain was subjected to random mutagenesis by UV. Among the different mutant strains obtained, only two showed interesting bio-functional characteristics, such as a good growth rate. The results demonstrated that the HM1010 mutant not only has a higher growth trend than the WT mutant but accumulates and produces ASX even in the green phase. This innovative genotype would guarantee the continuous production of ASX, not linked to the two-step process and the uniqueness of the product obtained.